Assessment of intra-individual variation in prostate-specific antigen levels in a biennial randomized prostate cancer screening program in Sweden. - Bruun, L; Becker, C; Hugosson, J; Lilja, H; Christensson, A (2005)
BACKGROUND: The degree of variability in prostate-specific antigen (PSA) measurements is important for interpreting test results in screening programs, and particularly for interpreting the significance of changes between repeated tests. This study aimed to determine the long-term intra-individual variation for PSA in healthy men. METHODS: A randomly selected cohort of men in a biennial prostate cancer screening program (ERSPC) conducted in Sweden from 1995-1996 to 2001-2002. We studied men who had total PSA (tPSA) levels < 2.0 ng/ml in 2001-2002. This included 791 men with tPSA < or = 0.61 ng/ml (group A), 1,542 men with tPSA < or = 0.99 ng/ml (group B), and 1,029 men with tPSA 1.00-1.99 ng/ml (group C). The intra-individual variability of free PSA (fPSA) and tPSA was assessed by calculating coefficients of variation (CV) for each individual's PSA measurements from the first and second round of screening (1995-1996 and 1997-1998). RESULTS: Intra-individual CV (geometric means) for tPSA were 13.7%, 12.7%, and 11.5% in groups A, B, and C, respectively. Corresponding CVs for fPSA were significantly lower, ranging from 12.1% to 10.4%. The estimated biological variation of tPSA and fPSA in groups A to C were 12.5%, 11.4%, 10.0% and 9.7%, 7.8%, 7.5%, respectively. CONCLUSIONS: In healthy men with PSA levels less than 2 ng/ml, the natural long-term variability for tPSA was less than 14%, and with 95% probability, a change in tPSA greater than 30% indicates a change beyond normal random variation.